2018
DOI: 10.1007/s00540-018-2532-6
|View full text |Cite
|
Sign up to set email alerts
|

Hypotension after induction of general anesthesia: occurrence, risk factors, and therapy. A prospective multicentre observational study

Abstract: GAIH rate depends on age, degree of blood pressure decompensation prior the surgery, and presence of diabetes mellitus type II.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
106
6
4

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 120 publications
(123 citation statements)
references
References 16 publications
7
106
6
4
Order By: Relevance
“…Hypotension is frequently observed as a side effect during induction of anesthesia using propofol [20][21][22]. A phase I clinical trial for remimazolam revealed that a 1-min bolus infusion of remimazolam 0.01-0.30 mg/kg did not cause hypotension, which was defined as systolic blood pressure lower than 80 mmHg, except one occurrence of hypotension 8 h after the dose of remimazolam [2].…”
Section: Hypotension: Side Effect Of Induction Agentmentioning
confidence: 99%
“…Hypotension is frequently observed as a side effect during induction of anesthesia using propofol [20][21][22]. A phase I clinical trial for remimazolam revealed that a 1-min bolus infusion of remimazolam 0.01-0.30 mg/kg did not cause hypotension, which was defined as systolic blood pressure lower than 80 mmHg, except one occurrence of hypotension 8 h after the dose of remimazolam [2].…”
Section: Hypotension: Side Effect Of Induction Agentmentioning
confidence: 99%
“…Hypertension is a common chronic condition in surgical patients requiring anesthesia [23][24][25]. ACE inhibitors and/ or angiotensin-receptor blockers (ARBs) are often used for perioperative blood pressure control in surgical patients with a history of hypertension and other cardiovascular diseases [23].…”
Section: Suggested Mechanism Of Covid-19mentioning
confidence: 99%
“…Conventional surgical options such as bypass grafting or arterial transposition are related with much higher blood loss than endovascular procedures and more perioperative complications [7,26]. General anaesthesia is linked with perioperative blood pressure drop, which in patients with multiple aortic arch syndrome might additionally lower the cerebral perfusion [27]. Endovascular procedures do not require general anaesthesia, so its impact on blood pressure is reduced.…”
Section: Is Minimally Invasive Treatment Still Possible In Multiple Ementioning
confidence: 99%